Simple Method of 9,10-Anthraquinone Assay in Eleutherine americana (Aubl.) Merr. ex K. Heyne using High-Performance Liquid Chromatography - Sophi Damayanti; Samuel Gunadi Tanusondjaja; Benny Permana; Rika Hartati; Dian Ayu Eka Pitaloka; Indra Wibowo (Indonesian Journal of Chemistry, 2021)
Eleutherine americana (E. americana) is a medicinal plant commonly found on the island of Borneo, Indonesia. This plant is known to have several biological activities. However, anthraquinone residues are generally present as contaminants. This study was aimed to develop a method of determining the levels of 9,10-anthraquinone in plant extracts and fractions using High Performance Liquid Chromatography (HPLC). The research aims to optimize the mobile phase, the system suitability test, and the system validation. The optimal mobile phase was acetonitrile:distilled water 1:1 v/v with a flow rate of 1.25 mL/min. The validation result shows that the linearity was obtained with a correlation coefficient (r) of 0.9995 and an r2 coefficient of 0.9991. The estimated limits for detection and quantification values were 0.178 and 0.594 µg/mL, respectively. In the intraday and inter-day accuracy test, the coefficient of variance for reference was 0.627 and 0.774, while the results for the sample were 2.966 and 2.658. The percentage recovery rate for reference was between 98.976–101.452%, and for the sample, the result was 89.191–94.667%. The average 9,10-anthraquinone content in the acetate fraction of E. americana plant was 9.799 µg/g ± 5.243.